Biological potential of Lophosoria quadripinnata fern extract: integration of UHPLC/ESI/QToF/MS analysis, antioxidant activity, molecular docking and molecular dynamics simulation - Torres-Benítez, Alfredo; Ortega-Valencia, José Erick; Salazar, Juan Rodrigo; Ley-Martínez, Jaqueline; Gallardo-Valdivia, Javian; Sánchez, Marta; Gómez-Serranillos, María Pilar; Vargas-Arana, Gabriel; Simirgiotis, Mario J. (Frontiers in Pharmacology, 2025)
Lophosoria quadripinnata (J.F.Gmel.) C.Chr., a fern species from the Dicksoniaceae family, is widely distributed in Central and South America. This study aimed to identify the bioactive compounds in the aqueous extract of L. quadripinnata, evaluate its antioxidant potential through in vitro analysis, and assess its neuroprotective effects via molecular docking and dynamics studies. Fourteen compounds were identified using ultra-high-performance liquid chromatography coupled with quadrupole-time-of-flight mass spectrometry (UHPLC-ESI-QToF-MS). In vitro assays revealed high concentrations of phenolic and flavonoid compounds, alongside significant antioxidant activity. Molecular docking studies, involving acetylcholinesterase (AChE), butyrylcholinesterase (BChE), tyrosinase, and the Nrf2-Keap1 protein complex, identified three compounds—5C3M (5-O-caffeoyl-3-O-malonylquinic acid), 5GDC (5-O-glucoside-6,7-dimethoxycoumarin), and irifloside—as promising inhibitors. These compounds exhibited favorable binding affinities, minimal toxicity, and strong interactions with key residues involved in the inhibition of the enzymes and protein complex. Additionally, molecular dynamics simulations revealed stable binding with AChE, BChE, and tyrosinase, with irifloside showing the highest binding affinity. The compounds also demonstrated the ability to modulate the Nrf2-Keap1 pathway, potentially enhancing the cellular antioxidant response. These findings suggest that L. quadripinnata contains bioactive compounds with significant potential for the development of neuroprotective agents, especially in oxidative stress-related diseases such as Alzheimer’s and Parkinson’s.